Analisis Potensi Masjid Kuno Gunung Pujut Sebagai Destinasi Wisata Budaya - Rahman, Riyandi Arif; Rumba , Rumba; supardi , supardi (Economics and Digital Business Review, 2024)
This research aims to analyze the potential of the Gunung Pujut Ancient Mosque as a cultural tourism destination. The Mount Pujut Ancient Mosque is located at the top of Mount Pujut, Sengkol Village, Pujut District, Central Lombok Regency, West Nusa Tenggara, and is a historical site with high architectural and cultural value. This research applies a qualitative descriptive method with data collection techniques through observation, interviews and documentation. Interviews were conducted with sources from the management, community and youth in the Gunung Pujut Ancient Mosque area which were then processed using SWOT analysis techniques. The research results show that the Gunung Pujut Ancient Mosque has great potential to be developed as a cultural destination because of its unique traditional architecture and long history in the spread of Islam on the island of Lombok. However, to achieve optimal development, cooperation with the government and community is needed to improve infrastructure, improve facilities and infrastructure, increase promotion and maintain cultural values. It is hoped that this research can become a reference in maximizing the potential of the Gunung Pujut Ancient Mosque as a sustainable cultural tourism destination.